Benefits of Using GIS-based Analysis on Site Selection and Location Decision for Student's Final Project, Study Case: Solar Energy Farm in Java, Indonesia - Muhammad Fahd Diyar Husni; Pramesti Putri Nugrahani (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
The use of GIS applications by architecture students is unusual, even though GIS has many tools to assist students’ projects, in this case, selecting and determining project site location plans for their final project. This study used the GIS application to determine the right location for a solar power plant project or a solar energy farm on Java Island, Indonesia. By determining what the suitable criteria for this project location are, there are 1). Ground Elevation, 2). The Sun Direction, 3). Ground Slope, and 4). Maximum Radiation. Those multiple criteria are used as determining factors with the Weight Overlay function in the GIS application. Overlaying all data and criteria maps will produce a final map that can be used as a reference for final decision-making. We can make our own rules to determine which places are the most appropriate by adjusting the weighting value per criteria. By using the GIS application and adjusting it to the regulatory conditions of the student’s project, it is clear that this application will significantly assist students in selecting and determining project locations in their Final Project.